2021
DOI: 10.1101/2021.03.04.433951
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sod1 Integrates Oxygen Availability to Redox Regulate NADPH Production and the Thiol Redoxome

Abstract: Cu/Zn superoxide dismutase (Sod1) is a highly conserved and abundant antioxidant enzyme that detoxifies superoxide by catalyzing its conversion to dioxygen and hydrogen peroxide. Using Saccharomyces cerevisiae and mammalian cells, we discovered that a major new aspect of the antioxidant function of Sod1 is to integrate oxygen availability to promote NADPH production. The mechanism involves Sod1-derived peroxide oxidatively inactivating the glycolytic enzyme, glyceraldehyde phosphate dehydrogenase (GAPDH), whic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 85 publications
(101 reference statements)
0
3
0
Order By: Relevance
“…Given the high degree of respiration required for meiosis, downregulation of Sod1 protein levels during this process may seem counterintuitive, but recent work argues that although it is best known for its antioxidant role, only a small fraction of this abundant enzyme is needed to protect cells from superoxide (Montllor-Albalate et al, 2019). This discrepancy was puzzling until Sod1 was found to play additional roles, including nutrient sensing and redox homeostasis (Reddi and Culotta, 2013;Montllor-Albalate et al, 2022). Identifying the specific roles that underlie its importance for meiosis is an interesting future area of research.…”
Section: Discussionmentioning
confidence: 99%
“…Given the high degree of respiration required for meiosis, downregulation of Sod1 protein levels during this process may seem counterintuitive, but recent work argues that although it is best known for its antioxidant role, only a small fraction of this abundant enzyme is needed to protect cells from superoxide (Montllor-Albalate et al, 2019). This discrepancy was puzzling until Sod1 was found to play additional roles, including nutrient sensing and redox homeostasis (Reddi and Culotta, 2013;Montllor-Albalate et al, 2022). Identifying the specific roles that underlie its importance for meiosis is an interesting future area of research.…”
Section: Discussionmentioning
confidence: 99%
“…PPP in response to oxidative stress. This study was found that under oxidative stress, conversion of superoxide into H 2 O 2 by Sod1 directly inhibits the TDH3-encoded glycolytic enzyme Gapdh which redirects carbon flux into the oxidative PPP(Montllor-Albalate et al, 2022). Conversely, loss of Sod1 (or its chaperone Ccs1) should derepress TDH3 regardless of the redox state, inhibiting the oxidative PPP.…”
mentioning
confidence: 91%
“…(Montllor-Albalate et al, 2022;Ralser et al, 2007). Hence, decreased NADPH consumption in mutants unable to assimilate sulphur should inhibit the oxidative PPP and improve E4P availability.…”
mentioning
confidence: 99%